High resolution sequence-directed mapping of nucleosomes with functional loads - Hapala, Jan; Trifonov, Edward N., 1937-; Masarykova univerzita. Přírodovědecká fakulta (2014)
V této dizertacní práci zkoumáme rotacní pozice nukleozomu v rídících sekvencích eukaryotických genomu: sestrihová místa, promotory obsahující TATA box a sekvence pripojené k jaderné matrix. Dále sledujeme výskyt nukleozomálního pozicního motivu ve ctyrech eukaryotických genomech. Výsledky našich analýz naznacují dosud neznámé funkce nukleozomu a jejich vliv na evoluci genomu.
In this dissertation we have investigated the rotational positioning of nucleosomes in the regulatory sequences of eukaryotic genomes: splice junctions, promoters containing TATA box and nuclear matrix. Further, we have studied occurrence of the nucleosome positioning motif in four eukaryotic genomes. Our results indicate yet unknown functions of nucleosomes and their influence on the evolution of the genomic DNA.
Vedoucí práce: Eduard Nikolajevič Trifonov
Dizertace (Ph.D.)--Masarykova univerzita, Přírodovědecká fakulta, 2014
Keywords: chromatin; nukleozomy; Chromatin; Nucleosomes; disertace; dissertations